2003
DOI: 10.1002/jssc.200301522
|View full text |Cite
|
Sign up to set email alerts
|

Direct resolution of novel tetrahedral metal clusters on a cellulose tris‐(3,5‐dimethylphenylcarbamate) chiral stationary phase by high‐performance liquid chromatography

Abstract: Direct resolution of novel tetrahedral metal clusters on a cellulose tris-(3,5-dimethylphenylcarbamate) chiral stationary phase by high-performance liquid chromatography Direct optical resolution of five novel tetrahedral heterometal cluster enantiomers has been achieved for the first time on a cellulose tris-(3,5-dimethylphenylcarbamate) chiral stationary phase, using hexane as the mobile phase with various alcohols as modifiers. UV detection was carried out at 254 nm. The influence of the mobile phase compos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…Grieb et al used porous carbon as a carrier of cellulose‐tris‐(3, 5‐dimethylphenylcarbamate) to prepare a CSP which showed a very good resolution for most of the analytes tested . Zhu et al found that the optical enantiomers of five novel tetrahedral isomeric clusters were directly resolved on a cellulose tris‐(3, 5‐dimethylphenylcarbamate) CSP . Weng et al used a sol‐gel method to obtain organic‐inorganic hybrids of cellulose (3, 5‐dimethylphenylcarbamate) functionalized silica particles, which achieved baseline separation of racemic 2, 2, 2‐trifluoro‐1‐ (9‐anthryl) ethanol …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Grieb et al used porous carbon as a carrier of cellulose‐tris‐(3, 5‐dimethylphenylcarbamate) to prepare a CSP which showed a very good resolution for most of the analytes tested . Zhu et al found that the optical enantiomers of five novel tetrahedral isomeric clusters were directly resolved on a cellulose tris‐(3, 5‐dimethylphenylcarbamate) CSP . Weng et al used a sol‐gel method to obtain organic‐inorganic hybrids of cellulose (3, 5‐dimethylphenylcarbamate) functionalized silica particles, which achieved baseline separation of racemic 2, 2, 2‐trifluoro‐1‐ (9‐anthryl) ethanol …”
Section: Introductionmentioning
confidence: 99%
“…31 Zhu et al found that the optical enantiomers of five novel tetrahedral isomeric clusters were directly resolved on a cellulose tris-(3, 5dimethylphenylcarbamate) CSP. 32 Weng et al used a sol-gel method to obtain organic-inorganic hybrids of cellulose (3, 5-dimethylphenylcarbamate) functionalized silica particles, which achieved baseline separation of racemic 2, 2, 2-trifluoro-1-(9-anthryl) ethanol. 33 Based on the special properties of two materials, we prepared a CSP material possessing the excellent advantages of functionalizing G and combining cellulose (3, 5-dimethylphenylcarbamate) in this work.…”
Section: Introductionmentioning
confidence: 99%
“…Our group is devoted to research for separation and preparative enantioseparation of racemates, including chiral organometallic compounds, etc. Although a series of chiral clusters had been discriminated by use of polysaccharide-derived chiral stationary phases [7,11,12,13], for some the resolution was too small to be used for their enantiopreparation. There is, therefore, a great need to explore the method used in the resolution of those compounds.…”
Section: Introductionmentioning
confidence: 99%